Analysis of Financial Statement Performance in the Textile Industry for the 2012-2021 Period - Faidatul Awwalien; Jufri, Achmad; Minhatus Salaamah; Ramiatin Lidia; Darmawan (International Journal of Economics, Business, and Entrepreneurship, 2023)
This study aims to determine the financial performance of three textile companies, namely PT. Asia Pacific Investama (MYTX), PT. Asia Pacific Fibers (POLY), and PT. Sri Rejeki Isman (SRIL) in the last ten years, 2012-2021. This study uses a quantitative-descriptive method with the type of data used is secondary data, obtained from the annual financial statements of each company at IDN Financial with the analysis using liquidity ratios including current ratio and quick ratio, solvency ratio including debt to assets ratio (DAR) and debt to equity ratio (DER), and profitability ratios include net profit margin (NPM) and return on assets (ROA) methods. The results based on the calculation of the liquidity ratio found that the performance of MYTX is not good, POLY is not good, and SRIL is quite good in the Current Ratio and Quick Ratio. In the solvency ratio, it was found that the performance of MYTX was quite good, POLY was not good, and SRIL was quite good in DAR. In contrast, the performance of the three companies is quite good in DER. And on the profitability ratios, it was found that the performance of the three companies is quite good in ROA or NPM.